2021
DOI: 10.4018/ijwltt.20211101.oa10
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effects of Self-Efficacy and Infrastructure on Teachers' ICT Use, an Extension of UTAUT

Abstract: The purpose of this empirical study was to investigate the effect of two important factors, self-efficacy and ICT infrastructure, on the teachers’ ability of ICT use in school pedagogy. The study employed a descriptive survey method within an ex-post-facto research design taking 400 teachers as samples from hundred purposively selected Indian secondary schools. Data were analyzed descriptively and inferentially. Results revealed that perception of self-efficacy and infrastructure were significant predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
3
4
1
Order By: Relevance
“…Second, the statistical results suggest that English preservice teachers’ self-efficacy in ICT has a strong positive association with their understanding of infrastructural support ( H2 : β = .57, ρ < 0.001). This result aligns with previous research findings [ 30 , 42 , 69 , 70 ]. Kundu et al [ 70 ] adopted the Unified Theory of Acceptance and Use of Technology (UTAUT) model [ 71 ] to examine how teachers’ self-efficacy and perceived infrastructure impact their ease of ICT use.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Second, the statistical results suggest that English preservice teachers’ self-efficacy in ICT has a strong positive association with their understanding of infrastructural support ( H2 : β = .57, ρ < 0.001). This result aligns with previous research findings [ 30 , 42 , 69 , 70 ]. Kundu et al [ 70 ] adopted the Unified Theory of Acceptance and Use of Technology (UTAUT) model [ 71 ] to examine how teachers’ self-efficacy and perceived infrastructure impact their ease of ICT use.…”
Section: Discussionsupporting
confidence: 93%
“…This result aligns with previous research findings [ 30 , 42 , 69 , 70 ]. Kundu et al [ 70 ] adopted the Unified Theory of Acceptance and Use of Technology (UTAUT) model [ 71 ] to examine how teachers’ self-efficacy and perceived infrastructure impact their ease of ICT use. Their findings revealed that in terms of facilitating ICT use, perceived infrastructure had a more pronounced individual effect than teachers’ self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…Research has demonstrated that individuals' technological behavioral intentions, which also indirectly implies his/ her perception that technology is beneficial, are strongly and positively influenced by self -efficacy (Kundu et al, 2021;Teo & Zhou, 2014). In the context of educational setting, Bakar, Maat, and Rosli (2020) research has shown that regardless of gender and teaching experience, teacher's self-efficacy plays a major role in influencing their intention to incorporate technology into their instructional methods, a finding that remains relevant around two decades later.…”
Section: Self-efficacymentioning
confidence: 99%
“…Facilitating conditions, which refer to the provision of required resources for effective technological utilization, are important factors in determining teachers' intention to use pedagogical technology tools. The provision of reliable technology, adequate training, and ongoing support are deemed essential elements driving teachers' decisions in incorporating technology in their classroom (Kundu, Bej, & Dey, 2021;Wang & Shih, 2009). According to Taimalu and Luik (2019) teachers' personal experience with tech-assisted teaching tools and alignment of the tools with their pedagogical style significantly impact their intent to leverage technology in classroom instructions.…”
Section: Introductionmentioning
confidence: 99%
“…This model is constantly evolving due to the addition of new factors or new interrelationships (Kundu et al, 2021). This was the case with the addition of the “IT Capability” factor (Shah et al, 2021) or the “Perceived self‐efficacy” factors (Agyei & Razi, 2022), giving a better explanation of the acceptance and use of innovative technologies and methodologies.…”
Section: Introductionmentioning
confidence: 99%